2019
DOI: 10.1016/j.gendis.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for chronic skin wounds in the era of personalized medicine: From bench to bedside

Abstract: With the significant financial burden of chronic cutaneous wounds on the healthcare system, not to the personal burden mention on those individuals afflicted, it has become increasingly essential to improve our clinical treatments. This requires the translation of the most recent benchtop approaches to clinical wound repair as our current treatment modalities have proven insufficient. The most promising potential treatment options rely on stem cell-based therapies. Stem cell proliferation and signaling play cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 166 publications
(183 reference statements)
0
76
0
9
Order By: Relevance
“…The endogenous population of adult stem cells play a pivotal role in cutaneous wound healing. It has been demonstrated that bone marrow-derived stem cells (BMDSCs) have the ability to migrate to the injured tissues, where they proliferate and differentiate into the required cell type, including fibroblasts [35]. It was estimated that up to 20% of fibroblasts at the wound site may originally derive from BMDSCs [36].…”
Section: Topical Delivery Of Adult Stem Cells' Suspensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endogenous population of adult stem cells play a pivotal role in cutaneous wound healing. It has been demonstrated that bone marrow-derived stem cells (BMDSCs) have the ability to migrate to the injured tissues, where they proliferate and differentiate into the required cell type, including fibroblasts [35]. It was estimated that up to 20% of fibroblasts at the wound site may originally derive from BMDSCs [36].…”
Section: Topical Delivery Of Adult Stem Cells' Suspensionmentioning
confidence: 99%
“…It was estimated that up to 20% of fibroblasts at the wound site may originally derive from BMDSCs [36]. Similarly, adipose tissue-derived stem cells (ADSCs) can differentiate and regenerate damaged skin tissue, whereas re-epithelialization of the wound occurs as a consequence of differentiation of interfollicular and hair follicle bulge epithelial stem cells toward keratinocytes [35]. Revascularization of the injured skin is the effect of either proliferation of endothelial cells in existing blood vessels (angiogenesis) or differentiation of endothelial progenitor cells (vasculogenesis).…”
Section: Topical Delivery Of Adult Stem Cells' Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone tissue engineering (BTE) emerged as a promising solution to overcome the limitations of auto- and allografts. BTE combines concepts from bone biology and engineering techniques to design scaffolds enriched with stem cells to repair large bony defects (Bishop et al, 2017 ; Coalson et al, 2019 ; Qasim et al, 2019 ; Karakuzu-Ikizler et al, 2020 ; Wang et al, 2020a ). However, bone tissue engineering practices have yet to be realized in clinical practice due to numerous limitations or lack of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been considerable advancements in the understanding of the biochemical pathways and mechanisms underlying skin regenerative therapies, leading to explorations into the use of cells and cell-derived cytokines and exosomes, as well as hydrogels (recently reviewed in [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]) ( Table 1 ). While decellularized dermal scaffolds are routinely employed [ 20 ], only a PDGF (Platelet Derived Growth Factor)-related product has received regulatory approval among the cytokines, while no cell therapy has widespread approval in the U.S. [ 21 , 22 ].…”
Section: Introduction—skin Wounds As a Medical Challengementioning
confidence: 99%